Super Turbo vs. Wonder Pig - Kirby, Lee (Fictitious character) (Super Turbo, 2018)
"When Wonder Pig starts to act strange, Super Turbo gets suspicious. Is it possible that the superhero guinea pig is actually working undercover for the evil rat Whiskerface?"--